Does going green pay off? The effect of an international environmental agreement on tropical timber trade - Stefan Borsky; Andrea Leiter; Michael Pfaffermayr (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2011)
Trade-related measures aim to regulate side-effects in international environmental agreements and are expected to positively influence the level of participation in the agreements as well as their degree of stability. In this paper we examine one side-effect of the 1994 International Tropical Timber Agreement - its impact on tropical timber trade. We use a cross-sectional dataset on bilateral trade flows of tropical timber that additionally contains information on trading partners' economic and geographical characteristics. Our empirical specification is based on a gravity equation, which is estimated using Heckman's selection model to address the potentially systematic selection of trading partners. We find significantly positive impacts of the 1994 ITTA on member countries' level of tropical timber trade. Furthermore, poor exporter countries benefit more from this trade enhancing effect than their richer counterparts.
Keywords: F53; Q23; Q27; F18; L15; 330; International environmental agreements; side benefits; bilateral trade flows; product quality; sample selection; Tropenholz; Umweltabkommen; Exportbeschränkung; Internationale Handelspolitik; Welt